POLE proofreading mutations elicit an anti-tumor immune response in endometrial cancer - Klenerman, P; Church, D; Tomlinson, I; van Gool, I; Eggink, F; Freeman-Mills, L; Stelloo, E; Marchi, E; de Bruyn, M; Palles, C; Nout, R; de Kroon, C; et al. (American Association for Cancer Research, 2015)
Purpose: Recent studies have shown that 7-12% of endometrial cancers (ECs) are ultramutated due to mutation in the proofreading exonuclease domain of the DNA replicase POLE. Interestingly, these tumors have an excellent prognosis. In view of the emerging data linking mutation burden, immune response and clinical outcome in cancer, we investigated whether POLE-mutant ECs showed evidence of increased immunogenicity. Design: We examined immune infiltration and activation according to tumor POLE proofreading mutation in a molecularly-defined EC cohort including 47 POLE-mutant tumors. We sought to confirm our results by analysis of RNAseq data from the TCGA EC series and used the same series to examine whether differences in immune infiltration could be explained by an enrichment of immunogenic neoepitopes in POLE-mutant ECs. Results: Compared to other ECs, POLE-mutants displayed an enhanced cytotoxic T cell response, evidenced by increased numbers of CD8+ tumor-infiltrating lymphocytes and CD8A expression, enrichment for a tumor-infiltrating T cell gene signature, and strong upregulation of the T cell cytotoxic differentiation and effector markers T-bet, Eomes, IFNG, PRF and granzyme B. This was accompanied by upregulation of T cell exhaustion markers, consistent with chronic antigen exposure. In-silico analysis confirmed that POLE-mutant cancers are predicted to display more antigenic neo-epitopes than other ECs, providing a potential explanation for our findings. Conclusions: Ultramutated POLE proofreading-mutant ECs are characterized by a robust intratumoral T cell response, which correlates with, and may be caused by an enrichment of antigenic neo-peptides. Our study provides a plausible mechanism for the excellent prognosis of these cancers.